Shexiang Tongxin Dripping Pills regulates SOD/TNF-α/IL-6 pathway to inhibit inflammation and oxidative stress to improve myocardial ischemia-reperfusion injury in mice - Du, Wanying; Zhai, Chenguang; Zhang, Huijie; Ren, Jun; Chen, Xiaoyang; Sun, Xuejing; Li, Chun; Wang, Wei; Chen, Yijun (Frontiers in Cardiovascular Medicine, 2025)
IntroductionShexiang Tongxin Dropping Pills (STDP), a traditional Chinese medicine (TCM), is clinically used for cardiovascular diseases like myocardial ischemia. Myocardial ischemia-reperfusion injury (MIRI), worsened by oxidative stress and inflammation, remains a significant problem, and the mechanisms underlying STDP's cardioprotection are incompletely understood. This study aimed to investigate STDP's effects on the SOD/TNF-α/IL-6 pathway and its impact on inflammation and oxidative stress in MIRI.MethodsA mouse model of MIRI was employed to evaluate the cardioprotective effects and mechanisms of STDP in vivo. Pretreatment with STDP was administered prior to MIRI induction. Assessments included serum SOD activity, cardiac tissue ROS levels, cardiomyocyte apoptosis rates (TUNEL assay), mRNA and protein expression of IL-1β, TNF-α, and IL-6 (qPCR, Western blot), histopathological evaluation of myocardial tissue morphology and inflammatory infiltration (H&E staining), myocardial infarction size (TTC staining), and cardiac function parameters (contractility, diastolic function).ResultsSTDP pretreatment significantly enhanced serum SOD activity and reduced cardiac ROS levels and cardiomyocyte apoptosis. It effectively downregulated mRNA and protein expression of IL-1β, TNF-α, and IL-6. Histopathology revealed reduced inflammatory cell infiltration and more intact cardiomyocyte morphology in STDP-treated groups. TTC staining confirmed a reduction in myocardial infarction size. Cardiac function assessments showed STDP improved both contractility and diastolic function post-MIRI and reduced arrhythmia incidence.DiscussionSTDP ameliorates MIRI in mice by inhibiting inflammatory responses and oxidative stress, primarily through modulation of the SOD/TNF-α/IL-6 pathway. Its cardioprotective effects include reducing apoptosis, inflammation, ROS, infarction size, and arrhythmias, while improving cardiac function and tissue repair. These findings elucidate a key mechanism for STDP and provide empirical support for its clinical use in MIRI, offering innovative perspectives for managing cardiovascular disorders with TCM and facilitating the integration of traditional and modern medicine.